Frequency of Boiled Potato Consumption and All-Cause and Cardiovascular Disease Mortality in the Prospective Population-Based HUNT Study - Moholdt, Trine; Nilsen, Tom I. L. (Frontiers in Nutrition, 2021)
Few studies have assessed the association between potato consumption and mortality, especially cardiovascular disease (CVD) mortality. Our objective was to investigate the association between consumption of boiled potatoes and all-cause and CVD mortality in a Norwegian population. We used data from the population based HUNT3 study in Norway, with data on boiled potato consumption frequency in 2006-2008 from 49,926 males and females aged 20 years or above. All-cause and CVD mortality were identified during 10 years follow-up through the national Cause of Death Registry, which is virtually complete. We used Cox regression to estimate hazard ratio (HR) with a 95% confidence interval (CI) for death controlling for potential confounders, and conducted additional analyses stratified by sex, body mass index (BMI) ±25 kg/m2, and age ±65 years. There were 4,084 deaths and 1,284 of these were due to CVD. Frequency of boiled potato consumption was not associated with all-cause mortality, nor with CVD mortality. Compared to those individuals who consumed boiled potatoes less than once weekly, those who reported to consume boiled potatoes 1-3 times per week had an adjusted HR (95% CI) of 1.12 (0.89, 1.41) for all-cause mortality and 1.20 (0.78, 1.86) for CVD mortality. Individuals who consumed boiled potatoes 4-6 times per week had HRs of 0.97 (0.78, 1.21) and 1.03 (0.68, 1.55), for all-cause and CVD mortality, respectively, whereas those who consumed boiled potatoes more than once daily had HRs of 1.04 (0.83, 1.29) and 1.09 (0.73, 1.63) for all-cause and CVD mortality, respectively. There was no evidence of differential associations for males versus females, nor between people with BMI ± 25 kg/m2. The associations between frequency of boiled potato consumption and all-cause mortality showed different patterns between those younger versus older than 65 years, with a tendency of increased risk only in the oldest age group. In conclusion, frequency of consumption of boiled potatoes was not associated with all-cause or CVD mortality in the HUNT population in Norway.